Recent developments in chemistry, coordination, structure and biological aspects of 1-(acyl/aroyl)-3-(substituted) thioureas - Saeed, Aamer (2017)
1-(Acyl/aroyl)-3-(substituted)thioureas are privileged architectures that have received remarkable attention of researchers in view of their variable topological aspects, binding modes and broad spectrum promising pharmacological properties. Reactivity of acyl thiourea derivatives has presented various organic transformations into other demanding scaffolds and this is an attractive strategy for synthetic chemists to access heterocyclic cores. Multiple binding sites make them flexible ligands for complexation with transition metals thus occupying a distinct position in coordination chemistry. 1-(Acyl/aroyl)-3-(substituted)thioureas have also emerged as attractive candidates in various fields such as ion sensors, corrosion inhibitors, molecular electronics, in metal extraction and in pharmaceuticals. The medicinal chemistry of this organo-sulfur framework and the derived metal complexes has witnessed fantastic progress in the current era. In continuation of our efforts to compile data on the structural aspects and numerous applications of 1-(acyl/aroyl)-3-(substituted)thiourea analogs, continuous advances have prompted us to present an overview of the last 2 years literature on this exciting family of compounds through this review article.